An Updated Review of Metal–Organic Framework Materials in Photo(Electro)Catalytic Applications: From co2 Reduction to Wastewater Treatments - Salazar-Gonzalez, R; Candia-Onfray, C; Candia-Onfray, C (Elsevier B.V., 2021)
This review summarizes recent advances in the development of metal–organic framework (MOF) materials, focusing on their photocatalytic and photoelectrocatalytic activities for different applications, such as CO2 reduction, water splitting, elimination of inorganic contaminants, and degradation of organic pollutants. In each section, the first applications described focus on the photocatalysts developed using MOF materials. Meanwhile, the latest are centered on photoelectrode applications using these materials. The last advances in the synthesis process are discussed in terms of improvement in electron transfer and charge separation, which enhance the activity of the photo (electro)catalysts. Finally, some insights about the upcoming applications of MOF materials are provided. © 2020 Elsevier B.V.